RETRACTED : The Effect of Non-Financial Compensation, Organizational Culture, and Work Stress on the Performance of Employees of the Directorate of Drug Investigation of Polda Metro Jaya in South Jakarta - Ayu Sri Rahayu; Elwisam Elwisam; Kumba Digdowiseiso (Journal of Social Science)
This research aims to review the influence of non financial compensation, organization culture and work stress on the performances of employee at Directorate of Drug Investigation Polda Mtero Jaya, South Jakarta. Research method used in this research that is quantitative descriptive with a population in this research is the employee of Directorate of Drug Investigation Polda Mtero Jaya, South Jakarta. There are four variables investigated in this study that is the non financial compensation (X1), organization culture (X2), work stress (X3) as independent variable and employee performance (Y) as dependent variable. Sample used in this research as many as 100 respondents. This research data using primary data in the form of a questionnaire the method of linear regression double processed using the software SPSS 17.0. The results of research based on linear regression shows that non financial compensation, organization culture, work stress positive influential and significant to employee performance.